Laser driver design in 65-nm CMOS technology for IFoF optical links - Paredes Páliz, Diego Fabián; Aznar, Francisco; Martínez, Antonio D.; Celma, Santiago (Jornada de Jóvenes Investigadores del I3A, 2021)
Broadband mobile networks have experimented an accelerated growth in the passed five decades culminating this development with 5G networks. This evolution demands an efficient and not expensive solution for optical-wireless front-end. Thus, information delivered by mobile stations is repeated over a Distributed Antenna System (DAS), where Remote Antenna Unit (RAU) integer optical and wireless modules. A non-linear response from light source means a major problem for an analog signal in comparison with digital one. The main problem with non linearity is signal dispersion giving as result alteration of signal shape form. In this direction there are some options from IC electronic design to interact with optical source, first the use of a linear drive circuit that delivers a certain amount of electric current for a voltage input signal, the second option is the use of pre-distortion or post-distortion electronic blocks to guarantee a lineal response from optical source. This work supposes a first approach and design of a linear laser driver in 65-nm CMOS technology that includes layout design.